Prediction Of Basic Wind Speed For Oman - Salim Almaawali, Said Saif (2017)
Sultanate of oman is a unique country with its distinct demographic and environmental characteristics typical to this country alone. It is also one of the fastest developing economies, giving rise to a spectacular construction spree seen over the last few years. Oman has no code of practices for wind loading for buildings yet. Hence, many designers adopted foreign codes of practice such as the british standards (bs8110, bs6399) in order to determine the value of basic wind speed for their building design. Such a practice is not appropriate on account of the prevailing differences in climatic and geographic conditions. Therefore, the aim of this study is to develop the value of basic wind speed map using collected daily wind speed from 13 meteorological stations all around oman. The characteristics of wind speed data have been determined using statistical measures such as mean, standard deviation, skewness, and kurtoses using spss software. Three statistical methods namely gumbel, gringorten and cunnane methods were used for two different distributions (gumbel and generalized pareto distributions) using three different data types (all data, peaks over threshold method (pot), and method of independent storms (mis).